Influence of occlusal forces on stress distribution in preloaded dental implant screws - EKİCİ, BÜLENT (MOSBY-ELSEVIER, 2004)
Statement of problem. Abutment and prosthetic loosening of single and multiple screw-retained, implant-supported fixed partial dentures is a concern. Purpose. The purpose of this study was to investigate stress distribution of preloaded dental implant screws in 3 implant-to-abutment joint systems under simulated occlusal forces. Material and methods. Three abutment-to-implant joint systems were simulated by using the 3-dimensional finite element analysis method: (1) Branemark external hexagonal screw-retained abutment, (2) ITI 8-degree Morse tapered cemented abutment, and (3) ITI 8-degree Morse tapered plus internal octagonal screw-retained abutment. A thermal load and contact analysis method were used to simulate the preload resulting from the manufacturers' recommended torques in implant screw joint assemblies. The simulated preloaded implants were then loaded with 3 simulated static occlusal loads (10 N; horizontal, 35 N; vertical, 70 N; oblique) on the crown position onto the implant complex. Results. Numeric and graphical results demonstrated that the stresses increased in both the abutment and prosthetic screws in the finite clement models after simulated horizontal loading. However, when vertical and oblique static loads were applied, stresses decreased in the external hexagonal and internal octagonal plus 8-degree Morse tapered abutment and prosthetic screws with the exception of the prosthetic screw of ITI abutment after 70-N oblique loading. Stresses increased in the ITI 8-degree Morse tapered cemented abutment after both vertical and oblique loads. Conclusion. Although an increase or decrease was demonstrated for the maximum calculated stress values in preloaded screws after occlusal loads, these maximum stress values were well below the yield stress of both abutment and prosthetic screws of 2 implant systems tested. The results imply that the 3 implant-to-abutment joint systems tested may not fail under the simulated occlusal forces.
Keywords: DYNAMIC FATIGUE PROPERTIES; FINITE-ELEMENT ANALYSIS; ABUTMENT INTERFACE; SYSTEMS; JOINT; STRENGTH